For Entertainment or Escaping From Reality: The Study of University Student Online Video Game Consumption in Malang, East Java Indonesia - Eskasasnanda, I Dewa Putu (Universitas Negeri Semarang, 2020)
This article aims to explain the cause and effect of excessive online video game consumption among university students in Malang City, East Java Indonesia. The informant of this study are university students who fond of playing online video games at late night and early morning in the internet cafe. The research discovers that: 1) living far away from parents, peers, and relatives often make university students feel lonely, this makes them use online video games to drive out their lonesome and boredom. By playing online video games, they can fulfill their social need by interacting with other players,Ã‚Â and finally, also get fun. 2) The negative side of online video games happens when the students play it excessively due to desire of escaping from real life problems. From this research, it can be revealed that there are similarity patterns among students experiencing online video games excessive consumption. These students are commonly suffering learning difficulties and they are isolated from friends because of taking study majors that are unmatched with their passion and interests. 3) No matter how harmful,Ã‚Â the games may endanger the studentÃ¢â‚¬â„¢s future, all of them feel not too worry. Life in young age and student status they still have made them no need to rush of thinking about their future. These facts are based on their opinion thatÃ‚Â becoming an adult and finding a job are still too far away to go